1999
DOI: 10.1007/s001250051297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin on in vitro vascular cell adhesion molecule-1 expression and in vivo soluble VCAM-1 release

Abstract: Although hyperinsulinaemia is an independent risk factor for the development of atherosclerotic lesions [1], mechanisms underlying the atherogenetic actions of insulin are largely unclear. Recent studies have shown that insulin exerts various endothelial effects, such as an increase of endothelin-1 and nitric oxide production [2]. These findings are of particular relevance and suggest insulin might also exert other endothelial effects which, in turn, could trigger and maintain the atherogenetic process.In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…Previous reports have shown that insulin can increase rolling and adhesion of monocytes to endothelial cells when pretreated with the PI3′-kinase inhibitor wortmannin, but the dependence of this on VCAM-1 had not been tested [8]. One report also described activation of the transcription factor nuclear factor-κB by insulin (consistent with our findings), but not the transcriptional activation of VCAM-1 in endothelial cells exposed to insulin [10], the latter possibly because lower-sensitivity techniques were used. Using a rotational adhesion assay we found that insulin per se (or even more together with PI3′-kinase inhibition by wortmannin) increases monocytoid cell adhesion, an effect related to the increase in VCAM-1 since largely inhibited by the blocking anti-VCAM-1 E1/6 antibody.…”
Section: Discussionsupporting
confidence: 86%
“…Previous reports have shown that insulin can increase rolling and adhesion of monocytes to endothelial cells when pretreated with the PI3′-kinase inhibitor wortmannin, but the dependence of this on VCAM-1 had not been tested [8]. One report also described activation of the transcription factor nuclear factor-κB by insulin (consistent with our findings), but not the transcriptional activation of VCAM-1 in endothelial cells exposed to insulin [10], the latter possibly because lower-sensitivity techniques were used. Using a rotational adhesion assay we found that insulin per se (or even more together with PI3′-kinase inhibition by wortmannin) increases monocytoid cell adhesion, an effect related to the increase in VCAM-1 since largely inhibited by the blocking anti-VCAM-1 E1/6 antibody.…”
Section: Discussionsupporting
confidence: 86%
“…This notion raises the possibility that the increased plasma levels of adhesion molecules found in obesity, dyslipidemia, hypertension, and type 2 diabetes are somehow related to insulin resistance and/or compensatory hyperinsulinemia. However, acute insulin infusion does not change plasma levels of adhesion molecules in both healthy subjects (9,10) and type 2 diabetic patients (11). This finding supports the conclusion that insulin resistance, rather than hyperinsulinemia, may be a factor contributing to the increased plasma levels of adhesion molecules in the clinical conditions mentioned above (12).…”
supporting
confidence: 69%
“…TNF-α, through increasing the activities of the NF-κB transcriptional factor [56, 57], protein kinase C [58], amino terminal kinase and inhibitor kinase, could cause serine/threonine phosphorylation of the insulin receptor substrate, interfere with normal phosphorylation of tyrosine, and weaken signal transduction of insulin, resulting in insulin resistance [36], otherwise, TNF-α may be result in the destruction of pancreatic beta cells and lead to the development of T1DM [59]. …”
Section: Discussionmentioning
confidence: 99%